An exhibition model to enable recognition and evaluation of creative works as research in interior design/ interior architecture - Lommerse, Marina; Lawrence, Jane; Mezhoud, Sven; Foster, Stuart (Curtin University of Technology, 2012)
Research ‘through’ design is a becoming’ field, which presents a challenge to designer/researchers. Recently, national research authorities have broadened their parameters to validate creative work in art, architecture and design. This study and the resulting model test the perceived ambiguity of the requirements provided by Australia’s Excellence in Research for Australia (ERA) and New Zealand’s Performance-Based Research Fund (PBRF) for creative works to be recognised as research through exhibition, and proposes a peer-reviewed model for interior design/interior architecture that can provide appropriate quality assurance processes for creative works.Designers and academics may be involved in a range of roles in developing an exhibition: as practitioners exhibiting work; as curators selecting works; as catalogue essay writers; as designers planning and designing the exhibition. These roles fall under the umbrella of creative practice and can be considered research activity under the ERA/ PBRF — assuming that research can be quality assured. To enable the critical engagement of research-based creative endeavours, the Interior Design/Interior Architecture Educators Association (IDEA) put forward an exhibition of creative works. A working party, established in 2011 to explore the potential of exhibition as research, used the 2012 IDEA exhibition An Interior Affair: a State of Becoming as a pilot (for this study). The aim is to set benchmarks in an area which has been contested and tenuous in terms of evaluation.The paper reviews previous research into exhibition as research, and compares and contrasts four national research frameworks (Australia, New Zealand, United Kingdom, South Africa) that recognise creative works as research, and exhibition as a validation and dissemination vehicle. We explore the range of quality assurance processes applicable for creative work as research in interior design/interior architecture, bearing in mind ‘what an exhibition’s essential contribution to knowledge might be, and how that contribution is to be archived and disseminated’ (Niedderer et al. (2006, 1). We examine a research-based gallery model to elucidate how these various quality assurance guidelines were interpreted in reality, and propose a model for peer review of research through design. We conclude with a review of the pilot model, which merges aspects of recognised curatorial and peer review approaches used in academic journals and conferences. We survey the existing constraints and the efficacy of our exhibition design as event.The pilot model validates the multitudinous interior design/interior architectural creative works evidencing a variety of research endeavors. As the publication of this paper precedes the actual exhibition, we expect that further research on the model will include an evaluation of the research in action at the event.